2007
DOI: 10.1212/01.wnl.0000276989.17578.02
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the glucocerebrosidase gene are associated with early-onset Parkinson disease

Abstract: This study suggests that the Glucocerebrosidase gene may be a susceptibility gene for Parkinson disease and that Glucocerebrosidase mutations may modify age at onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
222
8
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(244 citation statements)
references
References 46 publications
13
222
8
1
Order By: Relevance
“…In addition, GBA1-null mutations (84GG or IVS2+1) are associated with the highest risk for synucleinopathies, whereas a putative folding mutation N370S having the highest residual activity presents the lowest risk (38). Hence, the data suggest that mutations in GBA1 are sufficient to initiate aberrant α-syn folding but decrease in glucocerebrosidase activity (regardless of mutations) seems to accelerate misprocessing, and thereby increase the susceptibility and cause earlier onset of PD-like changes (8,39).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, GBA1-null mutations (84GG or IVS2+1) are associated with the highest risk for synucleinopathies, whereas a putative folding mutation N370S having the highest residual activity presents the lowest risk (38). Hence, the data suggest that mutations in GBA1 are sufficient to initiate aberrant α-syn folding but decrease in glucocerebrosidase activity (regardless of mutations) seems to accelerate misprocessing, and thereby increase the susceptibility and cause earlier onset of PD-like changes (8,39).…”
Section: Discussionmentioning
confidence: 91%
“…Emerging evidence suggests that mutations in GBA1 are the most common genetic risk factor for synucleinopathies, such as Parkinson disease (PD) and dementia with Lewy bodies (DLB), acting to modify the age of onset and disease progression (6)(7)(8)(9)(10)(11)(12)(13). The nervous system of subjects with PD and DLB typically shows abnormal accumulation of α-synuclein (α-syn) in Lewy bodies (LB) and Lewy neurites (LN) (14).…”
Section: D409v/d409vmentioning
confidence: 99%
“…However, significant differences in cognitive function between PD patients with and without GBA mutations were not confirmed in some studies [13,62,71,72]. It has been reported that there is significantly higher frequency of usage of acetylcholine esterase inhibitors for dementia in GBA PD compared with idiopathic PD [73], and one study found significant differences in selfreported cognitive impairment [74].…”
Section: Non Motor Featuresmentioning
confidence: 99%
“…For example, the average age of initial diagnosis for GBA1 mutation carriers is 4 years younger than that of non-carriers (Aharon -Peretz et al, 2004 ;Clark et al , 2007 ;Neumann et al , 2009 ). Moreover, more cognitive impairment, and less resting tremor and bradykinesia are reported in the PD of GBA1 mutation carriers (Goker -Alpan et al, 2008 ;Sidransky et al , 2009 ).…”
Section: Gba1 Mutations In Parkinson ' S Diseasementioning
confidence: 99%